(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This article talks about the activities of national cultural centers in Uzbekistan. The author, relying on scientific data, studied and analyzed the specific aspects of the activity of national cultural centers in Uzbekistan on the basis of available literature.